When Is a Child Too Young for Juvenile Court? A Comparative Case Study of State Law and Implementation in Six Major Metropolitan Areas - Abrams, Laura S. (Crime & delinquency, 2020)
There is a dearth of knowledge concerning statutes and practices designed to protect younger children from formal juvenile court petitions. This case study examines minimum age laws and related statutes in the six largest U.S. states and explores implementation of these policies and practices in major metropolitan areas within these states. The primary study methods included legal analysis and stakeholder interviews. Legal analysis identified diverse minimum age laws across states and complex statutes related to children's capacity to stand trial and competency. Stakeholders across the six cases agreed that the state should protect young children from formal delinquency petitions when possible. Discretionary statutes and practices appeared to play a key yet inconsistent role in excluding younger children from juvenile court.